Analysis of The Phytochemical Characteristics of Jasmine Flower Against Escherichia coli and Staphylococcus aureus - NATHASA WEISDANIA SIHITE; HERLA RUSMARILIN; MANUNTUN ROTUA (Microbiology Indonesia, 2021)
Indonesia is a famous country had the diversity of plants, especially agricultural product and herbs, they had a potential of antimicrobial as a like Jasmine Flower (Jasminum sambac Ait). This study Indonesia is a famous country had the diversity of plants, especially agricultural product and herbs, they had a potential of antimicrobial as a like Jasmine Flower (Jasminum sambac Ait). This study aimed to determine the phytochemical and antimicrobial activity of jasmine flower. Extraction was done by maceration, such as using water solvent, methanol, ethyl acetate, and hexane as the solvent. The sample bacteria used were Escherichia coli and Staphylococcus aureus. This study used disc diffusion method, with a complete 2-factor random design and 4 replications. Processing of the data is using ANOVA. The results showed that the jasmine extracts with a concentration of 25%, 50%, 75% and 100% had an effect to inhibit of the growth of the bacteria. Jasmine extract with ethyl acetate solvent was the most effective to inhibit the growth of bacteria. It was known that jasmine flower extract is one of the good natural antimicrobials gave an inhibitory effect to the growth of Escherichia coli and Staphylococcus aureus bacteria. Keywords: jasmine, Escherichia coli, Sthaphylococcus aureus, antimicrobials